UTILIZING EXTREME PROGRAMMING METHODOLOGY FOR DEVELOPING AN ANDROID-BASED SALESMAN VISITATION APPLICATION IN THE WATER TANK INDUSTRY - Jansen Wiratama; Sobiyanto, Sobiyanto; Yoto Theoderic, Felix (Universitas Serang Raya, 2023)
Integrating technology and industries has opened doors to new possibilities, leading to innovative solutions that reshape traditional practices. The water tank industry is an example that has witnessed significant technological influence as companies seek to optimize production processes, improve product quality, and enhance customer interactions. This article focuses on PT Sanggabuana Berjaya Indonesia (SBI), a company operating in the water tank industry in Indonesia. It discusses challenges related to conventional reporting methods for marketing visits and route determination for their marketing team. Previous studies in similar contexts have successfully addressed similar issues using technology, including GPS-based monitoring for location tracking and the development of mobile applications using the Extreme Programming (XP) model. Considering the relevant literature and interview results with SBI's sales manager, an Android-based monitoring application is proposed as a potential solution. The design process follows the System Development Life Cycle (SDLC) with the Extreme Programming (XP) model, covering planning, design, coding, and testing stages. Due to time and resource constraints, further stages of integration, delivery, retrospective, and continuous improvement are left for future work. This research proves that applying the extreme programming model in designing industry applications is quite relevant. The results of the black box testing tested show that all the features in the application can be used as needed. Keywords: Android, Extreme Programming, Mobile-application, Salesman, Water-tank.